2015
DOI: 10.1039/c5ra18528a
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging test of hydrogenated nitrile butadiene rubber using the time–temperature–strain superposition principle

Abstract: The long-term (~550 days) degradation of fracture strain of HNBR under the reference condition of 60 °C @ zero strain can be predicted using the time–temperature–strain superposition principle with the short-term (<10 days) test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…According to the equivalent principle of time and temperature, the increased frequency is equivalent to the shortened relaxation time of the material. Therefore, when the material is tested at a higher frequency, the transition peak of the segment movement could move to a higher temperature [ 33 , 34 ]. Different frequencies of 1 Hz to 20 Hz have the same effect of dynamic thermomechanical property on the silk fibroin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the equivalent principle of time and temperature, the increased frequency is equivalent to the shortened relaxation time of the material. Therefore, when the material is tested at a higher frequency, the transition peak of the segment movement could move to a higher temperature [ 33 , 34 ]. Different frequencies of 1 Hz to 20 Hz have the same effect of dynamic thermomechanical property on the silk fibroin.…”
Section: Resultsmentioning
confidence: 99%
“…In the glass transition region, when the semi-crystalline polymer material changes from the solid state to the flowing liquid state, the specific heat of the semi-crystalline polymer material undergoes a discontinuous mutation during the heating process [ 28 , 29 ]. Our previous studies on silk fibroin films by scanning electron microscopy (SEM) [ 30 ] and X-ray diffraction (XRD) [ 33 ] showed that a high CaCl 2 concentration can significantly reduce the silk fibril structure and micro-/nanoscale morphology in the silk film. Further, two small diffraction peaks appeared at 20.7° and 24.0° in the XRD curves of low CaCl 2 concentration sample (e.g., TSF-1.5), which is recognized as the silk I structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, chemical aging involves irreversible processes such as oxidation, chain scission, and additional crosslinking. The aging of elastomers such as hydrogenated nitrile butadiene rubber (HNBR) [3,4,5,6] and ethylene propylene diene rubber (EPDM) [7,8,9,10,11] as well as O-ring seals [12,13,14,15] has been investigated previously in numerous studies. During aging of EPDM, generally both chain scissions (mainly in the propylene segments [16]) and crosslinking reactions (mostly via the termonomer [8]) take place [17].…”
Section: Introductionmentioning
confidence: 99%
“…The accelerating effect of applied mechanical loading on aging has also been observed. [15][16][17] Xiong et al [15] studied the aging behavior of sulfured nitrile-butadiene rubber under the bending and tensile-bending stress, and calculated the storage life of NBR according to Arrhenius equation by the criterion of elongation.…”
Section: Introductionmentioning
confidence: 99%